Effects of triclosan on zebrafish early-life stages and adults - Oliveira, Rhaul
The biocide triclosan (TCS) is commonly used in personal care, acrylic, plastic, and textiles products. TCS has been detected in surface water in several countries, and its ecological impact is largely unknown. In this work, the toxicity of TCS in zebrafish (Danio rerio), embryos and adults was studied. Several lethal and sub-lethal endpoints were analysed in organisms exposed to TCS such as mortality, embryo development and behaviour, hatching, micronuclei and biochemical markers (cholinesterase (ChE), glutathione S-transferase (GST) and lactate dehydrogenase (LDH)). Embryo/larvae assay followed the OECD guideline on Fish Embryo Toxicity Test. Embryos were exposed at nominal concentrations of 0.1, 0.3, 0.5, 0.7 and 0.9 mg/l of TCS for 6 days and were inspected daily with the help of a stereomicroscopy for mortality, developmental parameters (otolith formation, eye and body pigmentation, somite formation, heart beat, tail circulation, detachment of the tail-bud from the yolk sac) and hatching. A similar test was run to obtain larvae for ChE, GST and LDH analysis. The adult test followed the OECD Guideline TG 203 in semi-static conditions. Adult zebrafish of similar length and age were exposed to nominal concentrations of 0.1, 0.2, 0.3, 0.4 and 0.5 mg/l of TCS for 96 h and were inspected daily for mortality and behaviour alterations. A second test was run to obtain organs for biomarkers analysis: Heads, muscles and gills were isolated and snap-frozen in eppendorfs and used for ChE, LDH and GST determinations, respectively. Adult zebrafish testing also comprised a third test for micronucleus analysis in which the nominal concentrations of 0, 0.175 and 0.350 mg/l were used. Peripheral blood was obtained by cardiac puncture and used for the analysis. TCS showed acute toxicity for embryo/larvae (96 h LC(50) = 0.42 mg/l) and delayed hatching. Moreover, embryo toxicity was evident: Delay on the otolith formation and eye and body pigmentation were found, and malformations were also evident, including spine malformations, pericardial oedema and undersize. Biomarkers levels were affected: ChE and LDH activity were increased in larvae exposed to 0.25 mg/l, and GST activity was increased in larvae exposed to 0.25 and 0.35 mg/l. TCS also demonstrated acute toxicity to adult zebrafish (96 h LC(50) = 0.34 mg/l). However, TCS did not change biomarkers levels and did not elicit a micronucleus in adults. Despite the fact that similar 96 h LC(50) values have been found for D. rerio embryos and adults (0.42 and 0.34 mg/l, respectively), the embryo assay was much more informative, showing important effects at several levels, including teratogenic response, hatching delay and alteration of biomarker levels. TCS does not seem to be genotoxic for adult fish or to interfere with biomarkers levels at the concentrations tested. TCS has deleterious effects on zebrafish adults and during early stages, (including embryotoxicity, hatching delay and alterations of biomarkers levels). The range of endpoints used on the embryo test allows an integrated analysis that contributes to a better understanding of the toxicity and mode of action of TCS. Future works should focus on a deeper investigation of TCS modes of action on zebrafish early-life stages. As embryo testing was revealed to be so informative, a refinement of the test could be made, including other endpoints such as different biochemical markers as well as DNA microarrays to assess a gene expression level for the effect of exposure to TCS. In the perspective of risk assessment, these endpoints should be explored in order to assess their usefulness as early warning signs and links should be sought between these short-term tests and effects of long-term exposures as it is observed in more realistic scenarios.